Taste Rules!: Food Marketing, Food Law, and Childhood Obesity in Canada - Elliott, Charlene (Cuizine)

(untitled) (McGill University Library, 2008)
AbstractFood marketing comprises a core part of the current food environment and is routinely identified as a main contributor to childhood obesity. Excess body weight affects over 26% of children in Canada—prompting a range of interventions to address the problem.Food policy and regulation form a key strategy in current attempts to combat the toxic environment, and this paper outlines the various modes of regulation that work to govern children’s “taste” in Canada. In particular, it details some of the promising, and problematic, aspects of seeking legal solutions to public health problems, especially when it comes to children and children’s food marketing.